If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(c + -1) + -18 = 12c + 2 Reorder the terms: 2(-1 + c) + -18 = 12c + 2 (-1 * 2 + c * 2) + -18 = 12c + 2 (-2 + 2c) + -18 = 12c + 2 Reorder the terms: -2 + -18 + 2c = 12c + 2 Combine like terms: -2 + -18 = -20 -20 + 2c = 12c + 2 Reorder the terms: -20 + 2c = 2 + 12c Solving -20 + 2c = 2 + 12c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12c' to each side of the equation. -20 + 2c + -12c = 2 + 12c + -12c Combine like terms: 2c + -12c = -10c -20 + -10c = 2 + 12c + -12c Combine like terms: 12c + -12c = 0 -20 + -10c = 2 + 0 -20 + -10c = 2 Add '20' to each side of the equation. -20 + 20 + -10c = 2 + 20 Combine like terms: -20 + 20 = 0 0 + -10c = 2 + 20 -10c = 2 + 20 Combine like terms: 2 + 20 = 22 -10c = 22 Divide each side by '-10'. c = -2.2 Simplifying c = -2.2
| 6sin^2+5cos=2 | | (2/3)^5= | | X-1=9.58 | | 18-(4m+4)=4+2m-14 | | 98/6 | | 2x-20=5x+9 | | 12x+0.5x+x=40 | | 2(f-8)=-30 | | 10(s-5)=-152 | | lnx=(1/8) | | 4k^2=9k | | 4(t+3)=-4 | | 7(25x+2)=0 | | 51.20=128-r*128 | | (7t+2)(t^2-5t-3)=0 | | 7(x+49)+28=14x-42+7x | | 3z^2-x-6=0 | | 2x=0.8x+54 | | 2x=0.8+54 | | 51.20=128-r^128 | | (4-x)(2x+1)=0 | | 6(3s+4)=168 | | 4x^6-4x^3+1=0 | | 7(2l+6)=98 | | 12y=2x+10 | | 6(5x+18)=378 | | 35X+10=180 | | 6(9x-2)=312 | | 5x+2=3x+22 | | 12x^4+17x^3+5x^2=0 | | (2z-7)(8-z)=0 | | -4y=2.32 |